USE OF ORGANIC MATTER AND SAND IN IMPROVING PROPERTIES OF SOME SOILS OF HOLY KARBALA GOVERNORATE AFFECTED BY PHENOMENON OF CRACKING - Adil Naser Abdulridha; Salman Khalaf Essa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was conducted to show the effect of cows’ manure, date palm residues, sand fraction and the interactions between them in treating the common cracking phenomenon in some soils of holy karbala governorate, and their role in improving some of the physical characteristics of those soils, represented in soil aggregates stability, modules of rupture, and linear expansion coefficient.Two agricultural sites were selected whose soils are characterized by heavy clay textures and widespread of cracking phenomenon within the holy Karbala governorate, the first was in Al-Kamaliya area and the second in Al-Khairat area. The results, showed a decrease in number of cracked masses, and their sizes in both studied soils. with an increase in levels of addition of animal manure, and plant residues and sand,and reached to lowest in treatments in which cracks disappeared while the highest values ​​of mean weight diameter were reached in the treatments in which cracks disappeared for the soil of two study sites. Results showed that the decreased values ​​of modules of rupture and linear expansion coefficient of soil with increasing the rates of addition and reaching to the lowest values ​​in the treatments in which cracks disappeared compared to reference treatment.